A note on Aladur, Alator and Arthur - Green, C (University of Wales Press, 2007)
A study of the Arthurian links and implications of the Book of Taliesin poem Kadeir Teyrnon. It is suggested that Arthur is the subject of the first part of this poem, and that the description of this subject as o echen aladur should be read as a indicating that he (Arthur) was ‘from the stock/lineage/family/tribe of (Mars) Alator’, a Romano-British deity. The exact import of this description is unclear, but it could have a significance beyond the merely laudatory.